2014
DOI: 10.1177/0961000614537514
|View full text |Cite
|
Sign up to set email alerts
|

Highly cited articles in the Information Science and Library Science category in Social Science Citation Index: A bibliometric analysis

Abstract: This study aims to identify and analyse the characteristics of highly cited articles published in the Information Science and Library Science category in the Social Science Citation Index. Articles that have been cited at least 100 times since publication up to the end of 2012 were analysed. We identified 501 highly cited articles published between 1956 and 2009 in 37 journals. MIS Quarterly published 26% of all analysed highly cited articles. The most productive researcher published 11 articles. Six bibliomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…There has been a long history in the investigations of citation trends of scientific articles . In recent years, there have been multiple studies reporting the citation life‐cycles of highly cited articles (TC year ≥100) in numerous Web of Science categories, including chemical engineering, materials science, and information science and library science . Results from these studies have shown that a highly cited article might not always have many citations in every year .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a long history in the investigations of citation trends of scientific articles . In recent years, there have been multiple studies reporting the citation life‐cycles of highly cited articles (TC year ≥100) in numerous Web of Science categories, including chemical engineering, materials science, and information science and library science . Results from these studies have shown that a highly cited article might not always have many citations in every year .…”
Section: Discussionmentioning
confidence: 99%
“…14 including chemical engineering, 23 materials science, 24 and information science and library science. 25 Results from these studies have shown that a highly cited article might not always have many citations in every year. 26 Therefore, extra indicators, such as the number of citations received in the year 2016 (C 2016 ) and in the publication year (C 0 ), might provide additional information for readers to understand the impact of a highly cited article today and immediately after publication.…”
Section: Discussionmentioning
confidence: 99%
“…These indicators include (1) total number of publications, (2) single author publication, (3) first author articles, (4) corresponding author articles, and (5) Y-index. [8] Order of authors is crucial to recognize who has the most substantial role in doing and reporting the research and to reveal the magnitude of authors' contribution. It is widely known that the first author has the major responsibility in the project's leadership and primary role for publication while the sec author is to contribute in article's analysis or writing.…”
Section: Authors and Publication Characteristics Of Authorsmentioning
confidence: 99%
“…Research has analyzed the research outcome from SSCI across different fields such asbusiness, business finance, economics, management, [3] nursing, [4] social work, [5] health care sciences and services, [6] psychiatry, [7] and information science and library science. [8] Bibliometric analyses have also been carried out on research from A and HCI to evaluate the quality of published work in various disciplines, for example dance [9] andreligions. [10] Linguistics category, like other categories, has a long history, dating back to the work of von Humboldt and Saussure in 19 th century and to the Bloomfield in the early 20 th century.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have analyzed the highly cited articles in recent times (Ho, 2014;Kolle, Shankarappa, & Ho, 2017;Kolle, Vijayashree, & Shankarappa, 2017). Several authors have studied the HCA in particular subject category such as education and educational research (Ivanoviae & Ho, 2016), horticulture , health care services (Hsu & Ho, 2014), environmental and occupational health (Smith, 2010), and malaria research . The bibliometric analysis of articles published in important journals in communication subject showed that the journal, Human Communication Research was the most influential journal within the communication subject (Reeves & Borgman, 1983).…”
mentioning
confidence: 99%